Modulation of Oxygen Content in Graphene Surfaces Using Temperature-Programmed Reductive Annealing Electron Paramagnetic Resonance and Electrochemical Study - Marciano, Ortal (Langmuir : the ACS journal of surfaces and colloids, 2016)
The oxidation level and properties of reduced graphene oxides (rGOs) were fine-tuned using temperature-programmed reductive annealing. rGOs were annealed at different temperatures (from 500 to 1000 °C) in hydrogen to modulate their oxidation levels. The surface of the rGOs was fully characterized using electron paramagnetic resonance backed by Raman, X-ray diffraction, and chemical analysis measurements. These experiments were used to study the changes in the surface of the rGO, its surface functionalities, and its defects as a function of the reduction temperature. In addition, electrochemical measurements to quantify the oxidation level of the rGOs offer a simple tool to correlate the properties of rGOs with their structure. Finally, we explored the effect of different levels of reduction on conductivity, capacitance, and surface reactivity. This research offers simple methodological techniques and routes to control and characterize the oxidation level of bulk quantities of rGO